The itineraries of art: topographies of artistic mobility in Europe and Asia - Gludovatz, Karin; Noth, Juliane; Rees, Joachim (Fink, 2015)
Introduction / Juliane Noth, Joachim Rees -- I. Art histories of the route : transcultural approaches: When routes entered culture : histories and politics of transcultural thinking (Annexe: Martin Beck, half modern, half something else) / Christian Kravagna. Tracking the routes of vision in early modern Eurasia / Monica Juneja. Why was there no Chinese painting of Marco Polo? / Eugene Y. Wang -- II. Symbolic itineraries and topographies : framing roads and routes: Geo-narrative in seventeenth-century China / Elizabeth Kindall. Historicity and the route : remarks on the relations between art and anthropology in the illustrations of the travel account of James Cook's third expedition / Sophie Annette Kranen. Itinerary and painting lineage : ten thousand miles along the Yangzi River in seventeenth-Century China / Julia Orell. Seen from a boat : travel and cultural history in Huang Binhong's landscape paintings / Juliane Noth -- III. Crossroads as contact zones : artefacts of interaction: Harbouring expectations : the littoral as contact zone in the visual arts of Japan and the Netherlands around 1600 / Joachim Rees, Nora Usanov-Geissler. Transcultural ballast : Netherlandish tiles as vehicles of exchange / Evelyn Reitz. Suspected prospects : art, topography, and identity in the Portsmouth area around 1800 / Ulrike Boskamp
Keywords: Konferenzschrift -- 2013 -- Berlin; Geschichte 1500-1900; Kunst; Interkulturalität; Kulturaustausch; Reise; Mobilität; Künstler; Asien; Europa; Geschichte 1580-1880